2016
DOI: 10.1186/s12879-016-2070-5
|View full text |Cite
|
Sign up to set email alerts
|

CD4-cell counts and presence of AIDS in HIV-positive patients entering specialized care—a comparison of migrant groups in the German ClinSurv HIV Cohort Study, 1999–2013

Abstract: BackgroundAlthough early presentation to HIV-care is essential to ensure timely initiation of antiretroviral therapy, recent studies have shown that especially migrants present to HIV-care at a later stage of HIV-infection. Currently, thirty percent of all newly diagnosed HIV cases in Germany originate from abroad. So far it is unknown, which specific migrant groups in Germany are particularly at risk for late presentation to HIV-care.MethodsWe used data from the Clinical Surveillance of HIV Disease (ClinSurv)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In the Netherlands from 1996–2014, the proportion of late presenters (defined as CD4 count < 350 cells/mm3) among migrants ranged from 63–79%, depending on region of origin [41]. More worrisome, in a German national cohort from 1999–2013, while median CD4 count at HIV diagnosis increased for native Germans and migrants from Central Europe, it did not change for other migrant groups over this time period [42].…”
Section: Entry Into Hiv Carementioning
confidence: 99%
“…In the Netherlands from 1996–2014, the proportion of late presenters (defined as CD4 count < 350 cells/mm3) among migrants ranged from 63–79%, depending on region of origin [41]. More worrisome, in a German national cohort from 1999–2013, while median CD4 count at HIV diagnosis increased for native Germans and migrants from Central Europe, it did not change for other migrant groups over this time period [42].…”
Section: Entry Into Hiv Carementioning
confidence: 99%
“…Characteristic of subject's age in this study had a standard deviation of 36.41 ± 9.82 years, with an age range of 17 years to 59 years. This age range is considered as productive age and sexually active, so that many may perform unprotected sexual behavior that is at risk of HIV transmission (4) . In terms of distribution of educational levels, there were still research subjects who did not complete elementary school (1; 0.9%), and 20 subjects (17.5%) had elementary school education.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of occupational backgrounds showed that 41 (36%) patients did not work. Patients with HIV / AIDS in the course of their illness will experience opportunistic infectious diseases that will affect the quality of life, one of which is occupation (2,4,13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that one quarter of newly HIV-diagnosed patients in Sweden had presented for health care with typical HIV/AIDS associated conditions without being HIV-tested 44 . Late HIV-diagnosis is associated with higher mortality and morbidity as well as increased risk of HIV transmission and higher health-care costs 44,173 . Although indicator-guided HIV-testing has been recommended in Europe since 2013 it is not yet widely implemented 44,54,[174][175][176] .…”
Section: Regarding High Grade Cervical Neoplasia As An Indicator Disementioning
confidence: 99%